Tacrolimus for Remission Induction and Maintenance Therapy in Patients with Ulcerative Colitis: A Retrospective Evaluation Study - Ayumi Ito; Bunei Iizuka; Teppei Omori; Shinichi Nakamura; Katsutoshi Tokushige (Gastroenterology Research and Practice)
Background. In this retrospective study, we compared the efficacy of tacrolimus (TAC) or prednisolone (PSL) for maintenance therapy in patients with ulcerative colitis (UC) at remission. Methods. The study patients were followed up for at least one year after induction of remission with either PSL (n=55, between April 2004 and March 2014) or TAC (n=40, between April 2009 and March 2014). The clinical features and relapse rates were compared in the two groups. Maintenance therapy in the TAC group included TAC alone, AZA alone, and TAC plus AZA. Results. The recurrence rates at 1500 days after remission were 61% and 46% for the PSL and TAC groups, respectively (P<0.05). The recurrence rates at 600 days for TAC, AZA, and TAC + AZA maintenance groups were 24%, 49%, and 55%, respectively. Nephrotoxicity developed in 16 patients on TAC maintenance therapy. Conclusions. TAC monotherapy is a potential alternative especially for PSL nonresponders or those intolerant to AZA. However, patients on TAC therapy should be regularly monitored for adverse effects including nephrotoxicity.